1 2 3 Action ! / Roslaili Anuar - Anuar, Roslaili (Faculty of Art and Design, 2021)
This is a digital artwork that uses photos and computer technology to create a unique piece of art. Turquoise blue and orange almost balance the two conservative colors, giving them a cool, refreshing vibe. Orange is the dominant hue in this piece, and it represents a warm or energetic atmosphere. It also connotes courage and hope in facing adversity. This color scheme represents a fresh mood that demands a delicate mix of taste and a powerful atmosphere. With the vivid turquoise and orange colors that were prominent in the 1950s and 1960s, the color scheme has an antique vibe. These combinations are contrasting with one another, resulting in a well-balanced mix of warmth and cold. The title 123 Action! was given to the artwork since they were once the most popular action movie on the silver screen, captivating viewers all over the world. In movies, the genuine pronunciation typically begin with 3 2 1 action, but it is intentionally referred to as 1 2 3 Action! to challenge the audience's ability to grab the connection. These characters were once idols and crazed by humans, but with the advent of a new revolution and a new stream in life, all of that has become a distant memory. The effects were utilized to give it a more contemporary appearance, making it more intriguing to look at. Contemporary art is defined as a reaction to modern art,